2018
DOI: 10.3390/md16120504
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic Activity of French Polynesian Padina pavonica Extract on Human Osteosarcoma Cells

Abstract: Recently, seaweeds and their extracts have attracted great interest in the pharmaceutical industry as a source of bioactive compounds. Studies have demonstrated the cytotoxic activity of macroalgae towards different types of cancer cell models, and their consumption has been suggested as a chemo-preventive agent against several cancers such as breast, cervix and colon cancers. Reports relevant to the chemical properties of brown algae Padina sp. are limited and those accompanied to a comprehensive evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Although unusual in the extraction of phenolic compounds due to the higher temperatures of the extraction involved, at least two studies have used the Soxhlet apparatus in the extraction of phenolic compounds from brown macroalgae, namely from the macroalga Sargassum wightii [56], from which some phlorotannins were identified after fractionation, and from Padina pavonica [92]. In this last study, the phenolic fraction was only characterized by spectrophotometric methods, namely, in terms of TPC, TFC, and total tannins content (TTC) (see Section 4.1).…”
Section: Conventional Solid-liquid Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although unusual in the extraction of phenolic compounds due to the higher temperatures of the extraction involved, at least two studies have used the Soxhlet apparatus in the extraction of phenolic compounds from brown macroalgae, namely from the macroalga Sargassum wightii [56], from which some phlorotannins were identified after fractionation, and from Padina pavonica [92]. In this last study, the phenolic fraction was only characterized by spectrophotometric methods, namely, in terms of TPC, TFC, and total tannins content (TTC) (see Section 4.1).…”
Section: Conventional Solid-liquid Extractionmentioning
confidence: 99%
“…The spectrophotometric characterization of the phenolic rich extracts from macroalgae involves mostly the estimation of TPC and TPhC, although some authors have also estimated the content of other specific families, such as flavonoids or anthocyanins [66,67,92,102,128]. The most commonly used method to determine the TPC in macroalgae extracts is the well-known Folin-Ciocalteu method, firstly established as Folin-Denis method [129] and then modified by Folin and Ciocalteu [130] and later by Singleton and Rossi [131].…”
Section: Global Analysis By Spectrophotometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Turbinaric acid, isolated from Turbinaria conoides from New Caledonia (Le Lann et al 2014) is a tris-nor-triterpene (C27), a derivative of squalene, which possesses cytotoxic properties (Kornprobst 2014). Studying brown seaweeds in French Polynesia, Bernardini et al (2018) highlighted interesting pharmacological and health-protecting effects, i.e. anti-proliferative and pro-apoptotic activities against two osteo-sarcoma cell lines, for phlorotannins isolated from Padina.…”
Section: Healthmentioning
confidence: 99%
“…Seaweeds are specifically used to treat tumors in CHM [116]. Several studies revealed that active metabolites among the terpenoids, including carotenoids, polyphenols and alkaloids that can obtained from marine source [117][118][119][120][121][122][123][124][125]. Compounds from natural sources with antiproliferative activity represent an important and novel alternative to treat several types of cancer.…”
Section: Herbal and Non-herbal Plant Derivativesmentioning
confidence: 99%